2023
DOI: 10.1007/s41116-023-00036-z
|View full text |Cite
|
Sign up to set email alerts
|

A history of solar activity over millennia

Abstract: Here we review present knowledge of the long-term behaviour of solar activity on a multi-millennial timescale, as reconstructed using the indirect proxy method. The concept of solar activity is discussed along with an overview of the dedicated indices used to quantify different aspects of variable solar activity, with special emphasis on sunspot numbers. Over long timescales, quantitative information about past solar activity is historically obtained using a method based on indirect proxies, such as cosmogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 491 publications
1
33
0
Order By: Relevance
“…The flux of GCR near Earth is modulated by solar magnetic activity on time scales ranging from hourly/daily to centennial/millennial, including periods of Grand solar minima, when the Sun is very quiet (see Usoskin, 2023, for a review). Although the GCR modulation process is complex (Potgieter, 2013), it is often parameterized for practical applications by a simple force‐field approximation (Caballero‐Lopez & Moraal, 2004; Usoskin et al., 2005), which includes a single modulation parameter ϕ in the units of rigidity and a prescribed local interstellar spectrum (LIS) of GCR.…”
Section: Methodsmentioning
confidence: 99%
“…The flux of GCR near Earth is modulated by solar magnetic activity on time scales ranging from hourly/daily to centennial/millennial, including periods of Grand solar minima, when the Sun is very quiet (see Usoskin, 2023, for a review). Although the GCR modulation process is complex (Potgieter, 2013), it is often parameterized for practical applications by a simple force‐field approximation (Caballero‐Lopez & Moraal, 2004; Usoskin et al., 2005), which includes a single modulation parameter ϕ in the units of rigidity and a prescribed local interstellar spectrum (LIS) of GCR.…”
Section: Methodsmentioning
confidence: 99%
“…The largest flare energy observed on our Sun is about 10 32 erg (e.g., Emslie et al 2012), while larger flares with the energy over 10 33 erg, referred to as "superflares," have never been reported in modern solar observations (e.g., Aulanier et al 2013). However, recent studies have identified multiple possible extreme solar energetic events with energies up to 10 34 erg that occurred in the past millennia using cosmogenic radionuclides ( 14 C, 10 Be, 36 Cl) recorded in tree rings and ice cores (e.g., Miyake et al 2019;Usoskin 2023). Furthermore, recent observations of solar-type (G-type main-sequence) stars have provided important insights into the rate of occurrence of superflares from the young solar-type stars and the analogs of the present-day Sun.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies are critical for understanding the frequency and impact of these events on our civilization and its infrastructures. Thus, superflares on solar-type stars have been highlighted from the context of solar physics (e.g., Aulanier et al 2013;Shibata et al 2013;Cliver et al 2022), planetary science (e.g., Fujii et al 2018;Linsky 2019;Airapetian et al 2020), biochemistry (e.g., Kobayashi et al 2023), and historical and geophysical studies (e.g., Miyake et al 2012;Hayakawa et al 2017;Usoskin 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses are particularly important because the powerful solar flares observed in WL are occasionally accompanied by major interplanetary coronal mass ejections (ICMEs) and solar energetic particles (SEPs), which can have major impacts on space weather and modern technological infrastructure (Usoskin 2023;Hudson 2021;Temmer 2021;Cliver et al 2022).…”
Section: Introductionmentioning
confidence: 99%